Perspectives on Inclusive Policies for Development in India: In Honour of Prof. R. Radhakrishna - Hashim, Saiyed R.; Mukherji, Rahul; Mishra, Brajaraja (India Studies in Business and Economics, 2022)
Inter-State Inequalities - Scope and Limits of Public Policy -- Macroeconomic Foundation of Functioning of the IMF: An Evolutionary Journey -- Indian Official Statistical System -- A Note on Unemployment and its Measurement in India -- Addressing Visible Inequalities: The Minimum Policy Agenda -- Accelerating Farm Income Growth: Opportunities and Challenges.